The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/wnr.0b013e32832d0a28
|View full text |Cite
|
Sign up to set email alerts
|

Brain protection by methylprednisolone in rats with spinal cord injury

Abstract: Traumatic spinal cord injury is clinically treated by high doses of methylprednisolone. However, the effect of methylprednisolone on the brain in spinal cord injury patients has been little investigated. This experimental study examined Bcl-2 and Bax protein expression and Nissl staining to evaluate an apoptosis-related intracellular signaling event and final neuron death, respectively. Spinal cord injury produced a significant apoptotic change and cell death not only in the spinal cord but also in the suprave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
1
16
0
3
Order By: Relevance
“…These results are conflicted with reports ranging from no cell death to extensive retrograde degeneration. 12,13, One of the limitations of these prior SCI studies is that they were performed over poorly defined areas of the cerebral cortex and/or did not involve rigorous quantitative assessment techniques. In contrast, our study utilizes stereology techniques with computer-driven, random, systematic sampling to provide unbiased and quantitative data for cell counting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are conflicted with reports ranging from no cell death to extensive retrograde degeneration. 12,13, One of the limitations of these prior SCI studies is that they were performed over poorly defined areas of the cerebral cortex and/or did not involve rigorous quantitative assessment techniques. In contrast, our study utilizes stereology techniques with computer-driven, random, systematic sampling to provide unbiased and quantitative data for cell counting.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al, 12 showed that SCI produced a significant apoptotic change and cell death not only in the spinal cord but also in the supraventricular cortex and hippocampal cornu ammonis 1 (CA1) region in the rat brains. The presence of hippocampal pathology after SCI was also suggested by Felix et al, 13 who described long-term reduction of neurogenesis in the hippocampus after subchronic cervical SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Chang et al (2009), os efeitos da metilpredinisolona são: inibição da peridoxidação e hidrólise de lipídeos, manutenção do fluxo sanguíneo tecidual e do metabolismo aeróbico, reversão do acúmulo de cálcio ionizado intracelular, redução da degradação de neurofilamentos e melhora da excitabilidade neuronal e transmissão axonal.…”
Section: Neuroproteção Regeneração E Transplante Celularunclassified
“…Apesar de este tratamento farmacológico promover bons resultados em relação à neuroproteção tanto na medula espinhal como no cérebro (Basso, 2000;Hulsebosch, 2002;Craig et al, 2002;Lim e Tow, 2007;Can et al, 2009;Chang et al, 2009), ele tem falhado em produzir uma recuperação funcional em modelos experimentais (Takami et al, 2002;Pereira et al, 2009). …”
Section: Neuroproteção Regeneração E Transplante Celularunclassified
“…De acordo com Tohda e Kuboyama (2011), a metilpredinisolona possui efeitos neuroprotetores por apresentar efeitos antioxidantes, melhorar a circulação sanguínea na medula espinhal, reduzir o influxo de cálcio, reduzir a degeneração walleriana e atenuar a perodoxicação lipídica. Apesar de este tratamento farmacológico promover bons resultados em relação à neuroproteção tanto na ME como no cérebro (Hulsebosch, 2002;Craig et al, 2002;Lim e Tow, 2007;Chang et al, 2009), ele tem falhado em produzir uma recuperação funcional em modelos experimentais (Takami et al, 2002;Pereira et al, 2009).…”
Section: Abordagens Terapêuticas 33unclassified